تحصص النص بالمصلحة المرسلة عند المالكية وتطبيقاتها المعاصرة - قدة, اسماعيل (University of Eloued جامعة الوادي, 2020)
يعتبر موضوع تخصيص النص بالمصلحة من أهم المباحث الأصولية التي تحتاج إلى الدراسة والضبط من أجل التنزيل الفقهي للمسائل المستجدة، وقد وقع الاختيار على العنوانالموسوم بـ: "تخصيص النص بالمصلحة المرسلة عند المالكية وتطبيقاتها المعاصرة"، وقد قمنا بتقسيمه إلى ثلاثة مباحث،وكل مبحث يشمل ثلاثة مطالب، حيث حوى المبحث الأول بيان معاني النص عند العلماء مع الإشارة إلى المعنى المراد من إطلاقه في عنوان مذكرتنا، كما حوى أقسام النص باعتبار العموم والخصوص مع توضيح معنى كل قسم وبيان دلالته الأصولية، ومما تضمنه أيضا تعريف كل من التخصيص والمصلحة وبيان أنواعهما، وأما المبحث الثاني فقد اشتمل على مفهوم أصل التخصيص بالمصلحة عند المالكية مع ذكر الشواهد الفقهية الدّالة عليه من مذهبهم، كما اشتمل أيضا على ضوابط العمل بهذا الأصل مع توضيح أهميته وفائدته الناتجة عن استعماله المضبوط في الاستنباط الفقهي، وأما المبحث الثالث فقد تضمن بعض التطبيقات الفقهية المعاصرة المتخرجة والمنطبقة على هذا الأصل في مجال العبادات والمعاملات المالية والطب، وفي الأخير ختمنا هذه الدراسة بخاتمة احتوت على أهم النتائج التي توصلنا إليها."The issue of personalizing the text is in the interest considered one of the most religious fundamental that need to be studied and set up for the purpose of jurisprudence projection of new issues. We have chosen the title tagged with: (Personalization the text with the sent interest with MALIKIAH and its contemporary applications). We have divided it into three sections, and each topic includes three under sections, where the first sections contained a statement of the meanings of the text with Muslim scholars, with reference to the meaning intended to be in the title of our study. It also contained sections of the text with regard to public and private, with clarification of the meaning of each section and indicating its religious fundamental significance, it also included the definition of both the Personalization and the interest and an indication of their types. As for the second section, it included the concept of the origin of Personalization in the interest of MALIKIAH, with mentioning the jurisprudential evidence of it in their doctrine. It also included controls on working with this religious fundamental, with clarification of its importance and usefulness resulting from its proper use in jurisprudential deduction. The third section included some contemporary jurisprudential applications applicable to this religious fundamental in the field of worship, financial transactions and medicine. Finally, we concluded this study with a conclusion that contained the most important results that we reached. "
مذكرة ماستر تخصص فقه مقارن واصوله
Keywords: التخصيص- المصلحة المرسلة-المالكية; "/ssignment - Sentinel - Malikiya "